Electroluminescent device and display device including the same

Through the blending solution process of quantum dots and single-molecular to low-molecular hole transport materials, the surface morphology and hole transport capability of the emission layer are optimized, and the insufficient hole transport capability and uneven surface in existing electroluminescent devices are solved. The problem is that the device life and light emission efficiency are improved.

CN110890471BActive Publication Date: 2025-01-17SAMSUNG ELECTRONICS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN201910842105.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-07
Filing Date
2019-09-06
Publication Date
2025-01-17
Estimated Expiration
2039-09-06

AI Technical Summary

Technical Problem

In existing electroluminescent devices, the hole transport capability and surface characteristics of the emitting layer are insufficient, resulting in low exciton quenching and light emission efficiency. The surface morphology is uneven when conventional hole transport materials blend with quantum dots, increasing leakage. Current and on-voltage reduce device life.

Method used

The emission layer is formed by blending the first hole transport material from quantum dots and a single molecule to low molecule, forming a uniform film through solution process, optimizing the surface morphology and hole transport capability of the emission layer, and reducing selectivity through different solvents Damage to the hole transport layer improves hole/electron carrier equilibrium.

Benefits of technology

The hole transmission capability and surface morphology of the emitting layer are improved, the leakage current and on-voltage are reduced, the life of the electroluminescent device is extended, and the luminous efficiency and maximum brightness are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN110890471B_ABST
    Figure CN110890471B_ABST
Patent Text Reader

Abstract

Disclosed are an electroluminescent device and a display device including the same. The electroluminescent device includes a first electrode and a second electrode facing each other; an emission layer disposed between the first electrode and the second electrode and including quantum dots and a first hole transport material having a substituted or unsubstituted C4-C20 alkyl group connected to a backbone structure; a hole transport layer disposed between the emission layer and the first electrode and including a second hole transport material; and an electron transport layer disposed between the emission layer and the second electrode.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS

[0002] This application claims priority to and the benefit of Korean Patent Application No. 10-2018-0107005 filed in the Korean Intellectual Property Office on September 7, 2018, the entire contents of which are incorporated herein by reference. Technical Field

[0003] Disclosed are an electroluminescent device and a display apparatus including the same. Background Art

[0004] Quantum dots are semiconductor nanocrystal materials with a diameter of several nanometers to tens of nanometers that show the quantum confinement effect. Compared with commonly used phosphors, quantum dots produce stronger light in a narrow wavelength region. Quantum dots emit light when excited electrons transition from the conduction band to the valence band, and the wavelength depends on the particle size and changes, even in the same material. Since the particle size of quantum dots is smaller, the wavelength of the light emitted is shorter, so by adjusting the size, they can obtain light in a desirable wavelength region.

[0005] In other words, compared to organic light-emitting diodes using emission layers containing phosphorescent and / or fluorescent materials, emission layers containing quantum dots and various electronic devices (apparatus) including the same can generally save manufacturing costs, and by changing the size of the quantum dots, desired colors can be emitted without using other organic materials in the emission layer to emit light of another color.

[0006] The luminous efficiency of the emission layer including quantum dots is determined by the quantum efficiency of the quantum dots, the balance of charge carriers, light extraction efficiency, etc. In particular, in order to improve the quantum efficiency, excitons may be confined in the emission layer, but when the excitons are not confined in the emission layer due to various factors, it may cause problems such as exciton quenching. Summary of the invention

[0007] Provided are an electroluminescent device having improved device characteristics by improving hole transport capability and surface characteristics of an emission layer and a display apparatus including the same.

[0008] According to one embodiment, an electroluminescent device includes a first electrode and a second electrode facing each other; an emission layer disposed between the first electrode and the second electrode and including quantum dots and a first hole transport material having a substituted or unsubstituted C4-C20 alkyl group connected to a backbone structure; a hole transport layer disposed between the emission layer and the first electrode and including a second hole transport material; and an electron transport layer disposed between the emission layer and the second electrode.

[0009] The first hole transport material may include a compound represented by Chemical Formula 1.

[0010] [Chemical formula 1]

[0011]

[0012] In Chemical Formula 1,

[0013] R 1 -R 8 independently selected from substituted or unsubstituted C4-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C3-C20 heteroaryl, substituted or unsubstituted C1-C20 alkylamine, substituted or unsubstituted C4-C20 (e.g. C6-C20) arylamine, and substituted or unsubstituted carbazolyl, with the proviso that R 1 -R 8 At least one of is a substituted or unsubstituted C4-C20 alkyl group,

[0014] When R 3 -R 8 When it is a substituted or unsubstituted C3-C20 cycloalkyl group, a substituted or unsubstituted C6-C20 aryl group, or a substituted or unsubstituted C3-C20 heteroaryl group, they are fused with the adjacent aromatic ring to provide a C8-C40 fused ring,

[0015] X 1 and X 2 are independently selected from N and C(-R a ), and X 3 and X 4 Independently selected from S, NR b , and C(-R c )(-R d )(where R a , R b , R c , and R d independently selected from substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, substituted or unsubstituted C6-C20 aryl, and substituted or unsubstituted C3-C20 heteroaryl),

[0016] L 1 and L 2 are independently selected from a single bond and a substituted or unsubstituted methylene or C2-C4 alkenylene, and

[0017] i, j, k, l, and m are independently 0 or 1.

[0018] The first hole transport material may include a compound represented by Chemical Formula 2.

[0019] [Chemical formula 2]

[0020]

[0021] Wherein, in Chemical Formula 2,

[0022] X 3 , X 4 , L 1 , L 2 , j, k, l, and m are the same as those defined in Chemical Formula 1,

[0023] R 1 -R 8 independently selected from substituted or unsubstituted C4-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C3-C20 heteroaryl, substituted or unsubstituted C1-C20 alkylamine, substituted or unsubstituted C4-C20 arylamine, and substituted or unsubstituted carbazolyl, with the proviso that R 1 -R 6 At least one of is a substituted or unsubstituted C4-C20 alkyl group, and

[0024] When R 3 -R 6 When it is one of a substituted or unsubstituted C3-C20 cycloalkyl group, a substituted or unsubstituted C6-C20 aryl group, or a substituted or unsubstituted C3-C20 heteroaryl group, they are condensed with the adjacent aromatic ring to provide a C8-C40 condensed ring.

[0025] R 1 -R 6 At least two of the may be substituted or unsubstituted C4-C20 alkyl groups.

[0026] The first hole transport material may include at least one of the compounds represented by Chemical Formula 2-1 to Chemical Formula 2-2.

[0027] [Chemical formula 2-1]

[0028]

[0029] [Chemical formula 2-2]

[0030]

[0031] In Chemical Formula 2-1 to Chemical Formula 2-2,

[0032] X 3 and X 4 Same as defined in Chemical Formula 1,

[0033] R 11, R 12 , R 13 , R 14 , R 15 , R 16 , R 21 , R 22 , R 23 , R 24 , R 25 , and R 26 are independently selected from substituted or unsubstituted C4-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, substituted or unsubstituted C6-C20 aryl, and substituted or unsubstituted C3-C20 heteroaryl, with the proviso that R 11 -R 14 At least one and R 21 -R 26 At least one of is a substituted or unsubstituted C4-C20 alkyl group,

[0034] R 27 and R 28 independently selected from substituted or unsubstituted C1-C20 alkylamine groups, substituted or unsubstituted C4-C20 arylamine groups, and substituted or unsubstituted carbazolyl groups, and

[0035] When R 13 , R 14 , R 15 、R1 6 , R 23 , R 24 , R 25 , and R 26 When it is one of a substituted or unsubstituted C3-C20 cycloalkyl group, a substituted or unsubstituted C6-C20 aryl group, or a substituted or unsubstituted C3-C20 heteroaryl group, they are condensed with the adjacent aromatic ring to provide a C8-C40 condensed ring.

[0036] The first hole transport material may include a compound represented by Chemical Formula 3.

[0037] [Chemical formula 3]

[0038]

[0039] In chemical formula 3,

[0040] X 3 , X 4 , L 1 , L 2 , j, k, l, and m are independently the same as defined in Formula 1, and

[0041] R 33 , R 34 , R 35, R 36 , R 37 , and R 38 independently selected from substituted or unsubstituted C4-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C3-C20 heteroaryl, substituted or unsubstituted C1-C20 alkylamine, substituted or unsubstituted C6-C40 arylamine, and substituted or unsubstituted carbazolyl, with the proviso that R 33 -R 38 At least one of is a substituted or unsubstituted C4-C20 alkyl group, and

[0042] When R 33 , R 34 , R 35 , R 36 , R 37 , and R 38 When it is one of a substituted or unsubstituted C3-C20 cycloalkyl group, a substituted or unsubstituted C6-C20 aryl group, or a substituted or unsubstituted C3-C20 heteroaryl group, they are condensed with the adjacent aromatic ring to provide a C8-C40 condensed ring.

[0043] R 33 -R 36 At least two of the groups may be unsubstituted C4-C10 linear or branched alkyl groups.

[0044] The first hole transport material may include at least one of the compounds represented by Chemical Formula A to Chemical Formula F.

[0045] [Chemical formula A]

[0046]

[0047] [Chemical formula B]

[0048]

[0049] [Chemical formula C]

[0050]

[0051] [Chemical formula D]

[0052]

[0053] [Chemical formula E]

[0054]

[0055] [Chemical formula F]

[0056]

[0057] The first hole transport material may have solubility in a non-polar solvent.

[0058] The first hole transport material may be included in an amount greater than or equal to about 2 wt % and less than about 50 wt % based on 100 wt % of the total weight of the emission layer.

[0059] The surface of the emission layer may have a root mean square roughness of about 0.5 to about 2.0 measured by atomic force microscopy (AFM).

[0060] The surface of the quantum dots may be bound with a hydrophobic ligand.

[0061] The quantum dots may include Group II-VI compounds, Group III-V compounds, Group IV-VI compounds, Group IV elements or compounds, Group I-III-VI compounds, Group I-II-IV-VI compounds, or combinations thereof.

[0062] The quantum dots may have a core-shell structure.

[0063] The second hole transport material and the first hole transport material may be different materials.

[0064] The second hole transport material may include poly(3,4-ethylenedioxythiophene) or a derivative thereof, poly(styrene sulfonate) or a derivative thereof, poly-N-vinylcarbazole or a derivative thereof, polyphenylenevinylene or a derivative thereof, polyp-phenylenevinylene or a derivative thereof, polymethacrylate, polyarylamine (polyarylamine), polyaniline or a derivative thereof, polypyrrole or a derivative thereof, poly(9,9-dioctylfluorene) or a derivative thereof, poly(spiro-bifluorene) or a derivative thereof, poly(N,N'-diphenyl-N,N'-di(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine), poly[(9,9-dioctylfluorene)-co-(4,4'-(N-(4-butylphenyl)-diphenylamine)], poly((9,9-dioctylfluorene)-co-N,N-diphenyl-N,N-di-(p-butylphenyl)-1,4-diaminobenzene), NiO, MoO 3 , or a combination thereof.

[0065] The electron transport layer may include inorganic material nanoparticles, a quinolone-based compound, a triazine-based compound, a quinoline-based compound, a triazole-based compound, a naphthalene-based compound, or a combination thereof.

[0066] The electron transport layer may include a cluster layer composed of inorganic material nanoparticles.

[0067] The electron transport layer may have a thickness of about 20 nm to about 100 nm.

[0068] The electroluminescent device may further include a hole injection layer between the first electrode and the hole transport layer.

[0069] According to another embodiment, a display device including the electroluminescent device is provided.

[0070] Provided are an electroluminescent device having improved device characteristics due to improved hole transporting ability and surface characteristics of an emission layer and a display apparatus including the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0071] Figure 1 is a schematic cross-sectional view of an electroluminescent device according to an embodiment,

[0072] Figure 2-5 is an atomic force microscope (AFM) image showing the surface morphology of the emission layer film (Comparative Example 1 ( Figure 2 ), Preparation Example 3 ( Figure 3 ), Preparation Comparative Example 2 ( Figure 4 ), and Preparation Example 5 ( Figure 5 )),

[0073] Figure 6-9 The scanning electron microscope image of the emission layer film (Comparative Example 3 ( Figure 6 ), Preparation Comparative Example 4 ( Figure 7 ), Preparation Example 10 ( Figure 8 ), and Preparation Example 11 ( Fig. 9 )),

[0074] Fig.10 is a graph showing the voltage-current density (log scale) characteristics of the electroluminescent devices according to Examples 1 to 4 and Comparative Example 1,

[0075] Fig.11 is a graph showing the voltage-current density (logarithmic scale) characteristics of the electroluminescent devices according to Examples 9 to 12 and Comparative Example 2,

[0076] Fig.12 is a graph showing the life characteristics of the electroluminescent devices according to Examples 2, 5, 11, and 14 and Comparative Examples 1 and 2, and

[0077] Fig.13 is a graph showing the life characteristics of the electroluminescent devices according to Examples 3, 6, 7, and 8 and Comparative Examples 1 and 2. DETAILED DESCRIPTION

[0078] Now will be described in detail below the example implementation of the present disclosure, and it can be easily performed by those with ordinary skills in the relevant field. However, the present disclosure can be embodied in many different forms and will not be construed as limited to the example implementations set forth herein.

[0079] In the accompanying drawings, the thickness of layers, films, panels, regions, etc. is exaggerated for clarity. The same reference numerals throughout the specification represent the same elements. It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it may be directly on the other element or there may be intermediate elements. Conversely, when an element is referred to as being "directly on" another element, there are no intermediate elements.

[0080] As used herein, the term "alkyl" refers to a group derived from a straight or branched saturated aliphatic hydrocarbon having a specified number of carbon atoms and having a valence of at least 1. Specific examples of the alkyl group may be methyl, ethyl, isopropyl, tert-butyl, n-octyl, n-decyl, n-hexadecyl, and the like.

[0081] As used herein, the term "alkenyl" refers to a linear or branched monovalent hydrocarbon group having at least one carbon-carbon double bond. Specific examples of the alkenyl group may be vinyl, allyl, 2-butenyl, 3-pentenyl, and the like.

[0082] As used herein, the term "alkynyl" refers to a linear or branched monovalent hydrocarbon group having at least one carbon-carbon triple bond. Specific examples of the alkynyl group may be propargyl, 3-pentynyl, and the like.

[0083] As used herein, the term "alkoxy" refers to "alkyl-O-," wherein the term "alkyl" has the same meaning as described above.

[0084] As used herein, the term "cycloalkyl" refers to a monovalent group having one or more saturated rings in which all ring members are carbon.

[0085] As used herein, the term "aryl" refers to an aromatic hydrocarbon group containing at least one ring and having a specified number of carbon atoms. The term "aryl" may be interpreted as including groups having an aromatic ring fused to at least one cycloalkyl ring.

[0086] As used herein, the term "aralkylene" refers to an alkylene group substituted with an aryl group.

[0087] As used herein, the term "heteroaryl" refers to an aryl group containing one to three heteroatoms selected from N, O, S, Si, and P as ring atoms and optionally substituted by one or more substituents at the indicated positions. Examples of heteroaryl groups include, but are not limited to, pyridyl, indolyl, carbazolyl, pyrimidinyl, pyridizinyl, pyrazinyl, imidazolyl, oxazolyl, furanyl, thienyl, thiazolyl, triazolyl, tetrazolyl, iso oxazolyl, quinolinyl, pyrrolyl, pyrazolyl, benzo[b]thienyl, isoquinolinyl, quinazolinyl, quinoxalinyl, thienyl, isoindolyl, and 5,6,7,8-tetrahydroisoquinolinyl.

[0088] As used herein, when no definition is otherwise provided, the term "heteroaralkylene" refers to an alkylene group substituted with a heteroaryl group.

[0089] As used herein, the terms "alkylene," "cycloalkylene," "arylene," and "heteroarylene" refer to divalent radicals derived from alkyl, cycloalkyl, aryl, and heteroaryl, respectively, as defined above.

[0090] As used herein, the term "alkylamine" refers to -NRR', wherein R and R' are each independently C1-C20 alkyl. As used herein, the term "arylamine" refers to -NRR', wherein R and R' are each independently C6-C30 aryl.

[0091] As used herein, when no definition is otherwise provided, the term "substituted" may refer to a compound or group in which a hydrogen atom is replaced by a substituent such as a C1-C30 alkyl, a C2-C30 alkenyl, a C2-C30 alkynyl, a C6-C30 aryl, a C7-C30 alkaryl, a C1-C30 alkoxyl, a C1-C30 heteroalkyl, a C3-C30 heteroalkaryl, a C3-C30 cycloalkyl, a C3-C15 cycloalkenyl, a C6-C30 cycloalkynyl, a C2-C30 heterocycloalkyl, a halogen (-F, -Cl, -Br, or -I), a hydroxyl (-OH), a nitro (-NO), or a 2 ), cyano (-CN), amino (-NRR', wherein R and R' are independently hydrogen or C1-C6 alkyl), azido (-N 3 ), amidino (-C(=NH)NH 2 ), hydrazino (-NHNH 2 ), hydrazone (=N(NH 2 )), aldehyde group (-C(=O)H), carbamoyl group (-C(O)NH 2), thiol group (-SH), ester group (-C(=O)OR, wherein R is C1-C6 alkyl or C6-C12 aryl), carboxyl group (-COOH) or its salt (-C(=O)OM, wherein M is an organic or inorganic cation), sulfonic acid group (-SO 3 H) or its salt (-SO 3 M, where M is an organic or inorganic cation), a phosphate group (-PO 3 H 2 ) or its salt (-PO 3 MH or -PO 3 M 2 , wherein M is an organic or inorganic cation), or a combination thereof.

[0092] As used herein, a "Group" may refer to a Group of the periodic table.

[0093] As used herein, “Group II” may refer to Group IIA and Group IIB, and examples of Group II metals may be Cd, Zn, Hg, and Mg, but are not limited thereto.

[0094] As used herein, examples of “Group II metal excluding Cd” may refer to Group II metals other than Cd, such as Zn, Hg, Mg, and the like.

[0095] As used herein, “Group III” may refer to Group IIIA and Group IIIB, and examples of Group III metals may be Al, In, Ga, and Tl, but are not limited thereto.

[0096] As used herein, "Group IV" may refer to Group IVA and Group IVB, and examples of Group IV metals may be Si, Ge, and Sn, but are not limited thereto. As used herein, the term "metal" may include semimetals such as Si.

[0097] As used herein, “Group I” may refer to Group IA and Group IB, and examples may include Li, Na, K, Rb, and Cs, but are not limited thereto.

[0098] As used herein, “Group V” may refer to Group VA, and examples may include nitrogen, phosphorus, arsenic, antimony, and bismuth, but are not limited thereto.

[0099] As used herein, "Group VI" may refer to Group VIA, and examples may include sulfur, selenium, and tellurium, but are not limited thereto.

[0100] First, refer to Figure 1 , describing a schematic structure of an electroluminescent device according to an embodiment.

[0101] Figure 1 is a schematic cross-sectional view of an electroluminescent device according to an embodiment.

[0102] According to an embodiment, the electroluminescent device 10 includes a first electrode 110 and a second electrode 160 facing each other and an emission layer 140 disposed therebetween and including quantum dots 141 and a first hole transport material having a substituted or unsubstituted C4-C20 alkyl group connected to a skeleton structure, a hole transport layer 130 disposed between the first electrode 110 and the emission layer 140 and including a second hole transport material, a hole injection layer 120 disposed between the first electrode 110 and the hole transport layer 130 but which may be omitted in consideration of its relationship with each constituent element, and an electron transport layer 150 disposed between the emission layer 140 and the second electrode 160.

[0103] In other words, the electroluminescent device 10 may have a stack structure in which the hole injection layer 120, the hole transport layer 130, the emission layer 140, and the electron transport layer 150 are disposed between the first electrode 110 and the second electrode 160 facing each other.

[0104] In one embodiment, the first electrode 110 may be directly connected to a driving power source and thus may function to allow current to flow to the emission layer 140. The first electrode 110 may include a material having light transmittance in at least the visible light wavelength region. For example, the material included in the first electrode 110 may further have light transmittance for light in the infrared or ultraviolet (UV) wavelength region. For example, the first electrode 110 may be made of an optically transparent material.

[0105] In one embodiment, the first electrode 110 may include molybdenum oxide, tungsten oxide, vanadium oxide, rhenium oxide, niobium oxide, tantalum oxide, titanium oxide, zinc oxide, nickel oxide, copper oxide, cobalt oxide, manganese oxide, chromium oxide, indium oxide, or a combination thereof.

[0106] However, the first electrode 110 according to the embodiment is not necessarily limited thereto but may include a semi-transmissive material that selectively transmits light in a specific wavelength region and perform a function of reflecting light in a visible light wavelength region and folding it back toward the second electrode 160 .

[0107] Meanwhile, in an embodiment, the first electrode 110 may be disposed on the substrate 100, such as Figure 1 As shown in . The substrate 100 may be a transparent insulating substrate or may be made of a ductile material. The substrate 100 may include glass or a polymer material in the form of a film having a glass transition temperature (Tg) greater than about 150° C. For example, it includes a material based on COC (cyclic olefin copolymer) or COP (cyclic olefin polymer).

[0108] In an embodiment, the substrate 100 may support the hole injection layer 120, the hole transport layer 130, the emission layer 140, and the electron transport layer 150 disposed between the first electrode 110 and the second electrode 160. However, the substrate 100 of the electroluminescent device 10 according to the embodiment may not be disposed under the first electrode 110, but the substrate 100 may be disposed on the second electrode 160 or may be omitted when necessary.

[0109] The second electrode 160 includes an optically transparent material and may function as a light-transmitting electrode to transmit light generated in the emission layer 140. In one embodiment, the second electrode 160 may include at least one selected from the group consisting of silver (Ag), aluminum (Al), copper (Cu), gold (Au), and alloys thereof, molybdenum oxide, tungsten oxide, vanadium oxide, rhenium oxide, niobium oxide, tantalum oxide, titanium oxide, zinc oxide, nickel oxide, copper oxide, cobalt oxide, manganese oxide, chromium oxide, indium oxide, or a combination thereof.

[0110] However, the second electrode 160 according to the embodiment is not necessarily limited thereto, but may include a semi-transmissive material that selectively transmits light in a specific wavelength region and perform a function of reflecting light in a visible light wavelength region and folding it back toward the first electrode 110 .

[0111] When the second electrode 160 functions as a reflective electrode, the first electrode 110 may be a light-transmitting electrode formed of a material that transmits light in at least a visible wavelength region or a semi-transmitting electrode that selectively transmits light in a specific wavelength region.

[0112] Each of the first electrode 110 and the second electrode 160 may be formed by depositing a material for forming an electrode on the substrate 100 or the organic layer through a method such as sputtering.

[0113] On the other hand, Figure 1 As shown in , the electroluminescent device 10 according to the embodiment may have a general structure in which a substrate 100 and respective constituent elements are disposed in the above stacking order.

[0114] However, the electroluminescent device 10 according to the embodiment is not necessarily limited thereto, but may have a variety of structures within the range of satisfying the aforementioned order of setting each constituent element. For example, when the substrate 100 is not disposed under the first electrode 110 but disposed on the second electrode 160, the electroluminescent device 10 may have an inverted structure.

[0115] The hole injection layer 120 may be directly disposed on the first electrode 110. The hole injection layer 120 may supply holes into the emission layer 140 through the hole transport layer 130. However, the hole injection layer 120 may be omitted in consideration of the thickness and material of the hole transport layer 130.

[0116] The hole injection layer 120 may be formed of a p-type semiconductor material or a material doped with a p-type dopant. For example, the hole injection layer 120 may include PEDOT [poly (3,4-ethylenedioxythiophene)] or a derivative thereof, PSS [poly (styrene sulfonate)] or a derivative thereof, poly-N-vinyl carbazole (PVK) or a derivative thereof, polyphenylene vinylene or a derivative thereof, poly-p-phenylene vinylene (PPV) or a derivative thereof, polymethacrylate, poly (9,9-dioctylfluorene) or a derivative thereof such as poly [(9,9-dioctylfluorene-2,7-diyl-co-(4,4'-(N-4-butylphenyl) diphenylamine] or poly ((9,9-dioctylfluorene)-co-N,N'-diphenyl-N,N'-di-(p-butylphenyl)-1,4-diaminobenzene), poly (spiro-bifluorene) or a derivative thereof, TCTA ( tris(4-carbazol-9-ylphenyl)amine), TPD (N,N'-diphenyl-N,N'-di(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine), NPB (N,N'-di(naphthalene-1-yl)-N-N'-diphenyl-benzidine), m-MTDATA (tris(3-methylphenylphenylamino)-triphenylamine), TFB (poly[(9,9-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-4-butylphenyl)diphenylamine)]), PFB (poly[(9,9-dioctylfluorene)-co-(N,N'-diphenyl-N,N'-di-(p-butylphenyl)-1,4-diaminobenzene)]), poly-TPD, metal oxides such as NiO and MoO 3 , or a combination thereof, but not limited thereto.

[0117] The hole transport layer 130 may be disposed on the first electrode 110, for example, on the first electrode 110 and the hole injection layer 120. The hole transport layer 130 may provide and transport holes into the emission layer 140. The hole transport layer 130 may be formed directly under the emission layer 140 and directly contact the emission layer 140.

[0118] In one embodiment, the hole transport layer 130 includes a second hole transport material. The second hole transport material may be a p-type semiconductor material or a material doped with a p-type dopant.

[0119] In one embodiment, the second hole transport material included in the hole transport layer 130 may be a material different from a first hole transport material of the emission layer 140 to be described later. In one embodiment, the second hole transport material may be a polymer, an oligomer, a metal oxide, or a combination thereof.

[0120] Examples of the second hole transport material may include poly(3,4-ethylenedioxythiophene) or a derivative thereof, poly(styrene sulfonate) or a derivative thereof, poly-N-vinylcarbazole or a derivative thereof, polyphenylenevinylene or a derivative thereof, polyparaphenylenevinylene or a derivative thereof, polymethacrylate, polyarylamine, polyaniline or a derivative thereof, polypyrrole or a derivative thereof, poly(9,9-dioctylfluorene) or a derivative thereof, poly(spiro-bifluorene) or a derivative thereof. Compounds, poly-(N,N'-diphenyl-N,N'-di(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine), poly[(9,9-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-4-butylphenyl)diphenylamine)], poly[(9,9-dioctylfluorene)-co-(N,N'-diphenyl-N,N'-di-(p-butylphenyl)-1,4-diaminobenzene)], NiO, MoO 3 , or a combination thereof, but not limited thereto.

[0121] When the hole transport layer 130 is made of a polymer, an oligomer, a metal oxide, or a combination thereof as a second hole transport material, the life of the electroluminescent device 10 can be increased, and the turn-on voltage of the electroluminescent device 10, which is an operation start voltage, can be reduced. In particular, when the second hole transport material is selected from the above materials, the surface morphology of the hole transport layer 130 directly in contact with the emission layer 140 can be uniformly controlled compared to when a single molecule hole transport material is used. Therefore, the leakage path of the holes moving from the hole transport layer 130 to the emission layer 140 is minimized, so that the leakage current and the driving voltage can be reduced.

[0122] For example, the hole transport layer 130 may be formed by a wet coating method such as spin coating, etc. For example, both the hole transport layer 130 and the emission layer 140 may be formed by a wet coating method. In this way, the hole transport layer 130 and / or the emission layer 140 may be formed by a simple process.

[0123] In addition, in one embodiment, the hole transport layer 130 and the emission layer 140 may be made of materials having relatively different solubilities. For example, the material for the hole transport layer 130 has improved solubility in an aromatic non-polar solvent, and the material for the emission layer 140 has improved solubility in an aliphatic non-polar solvent. After dissolving the material for the hole transport layer 130 in an aromatic non-polar solvent, dissolving the material for the emission layer 140 in an aliphatic non-polar solvent, and then performing a solution process, the hole transport layer 130 and the emission layer 140 may be sequentially formed without damaging the surface of the previously formed hole transport layer 130.

[0124] For example, when forming a TFB polymer film as the hole transport layer 130, a precursor solution including a TFB precursor polymer and an aromatic non-polar solvent (eg, toluene, xylene, etc.) is spin-coated on the first electrode 110 or the hole injection layer 120. 2 The hole transport layer 130 made of TFB is formed by heat treating in an inert gas atmosphere or in a vacuum at a temperature of about 150°C to about 180°C for about 30 minutes, and an aliphatic non-polar solvent (e.g., octane, nonane, cyclohexane, etc.) can be used to dissolve the material for the emission layer 140 to easily form the emission layer 140 thereon using a solution process.

[0125] In this way, when the solvent selectivities of the hole transport layer 130 and the emission layer 140 are relatively different from each other, both the hole transport layer 130 and the emission layer 140 can be formed using a solution process, and thus the process can be conveniently performed and damage to the hole transport layer 130 caused by an organic solvent or the like during the formation of the subsequent emission layer 140 can be minimized through different solvent selectivities.

[0126] The emission layer 140 may be disposed on the hole transport layer 130 and may include quantum dots 141 and a first hole transport material.

[0127] The emission layer 140 is a place where electrons and holes transferred by current supplied from the first electrode 110 and the second electrode 160 are recombined to generate excitons, and the generated excitons transition from an excited state to a ground state to emit light of a wavelength corresponding to the size of the quantum dot 141. That is, the quantum dot 141 can give the emission layer 140 an electroluminescent function.

[0128] In particular, the quantum dots 141 have a discontinuous energy band gap due to the quantum confinement effect and the incident light may be converted into light having a specific wavelength and then radiated. Therefore, the emission layer 140 including the quantum dots 141 may generate light having excellent color reproducibility and color purity.

[0129] For example, the emission layer 140 may emit light in a predetermined wavelength region. The predetermined wavelength region belongs to the visible light region, for example, one of the following: a first wavelength region of about 380 nm to about 488 nm, a second wavelength region of about 490 nm to about 510 nm, a third wavelength region of greater than about 510 nm to less than or equal to about 580 nm, a fourth wavelength region of about 582 nm to about 600 nm, and a fifth wavelength region of about 620 nm to about 680 nm.

[0130] In one embodiment, the material of the quantum dot 141 is not particularly limited and known or commercially available quantum dots may be used. For example, the quantum dots 141 according to the embodiment may each include a II-VI group compound, a III-V group compound, a IV-VI group compound, a IV group element or compound, an I-III-VI group compound, an I-II-IV-VI group compound, or a combination thereof.

[0131] For example, the quantum dots 141 according to the embodiment may each include a II-VI compound, a III-V compound, a IV-VI compound, a IV element or compound, an I-III-VI compound, a I-II-IV-VI compound not including Cd, or a combination thereof. That is, the quantum dots 141 according to the embodiment may each be a non-cadmium-based quantum dot. As such, when the quantum dots 141 are composed of non-cadmium-based materials, they are not toxic and therefore not dangerous and are environmentally friendly compared to conventional cadmium-based quantum dots.

[0132] The II-VI group compound may be selected from: a binary compound selected from ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, MgSe, MgS, and mixtures thereof; a ternary compound selected from ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, HgZnS, HgZnSe, HgZnTe, MgZnSe, MgZnS, and mixtures thereof; and a quaternary compound selected from HgZnTeS, HgZnSeS, HgZnSeTe, HgZnSTe, and mixtures thereof. The II-VI group compound may further include a group III metal.

[0133] The III-V compound may be selected from: a binary compound selected from GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, and a mixture thereof; a ternary compound selected from GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, InZnP, and a mixture thereof; and a quaternary compound selected from GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb, and a mixture thereof. The III-V compound may further include a Group II metal (InZnP).

[0134] The IV-VI group compound may be selected from: a binary compound selected from SnS, SnSe, SnTe, PbS, PbSe, PbTe, and mixtures thereof; a ternary compound selected from SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, and mixtures thereof; and a quaternary compound selected from SnPbSSe, SnPbSeTe, SnPbSTe, and mixtures thereof. Examples of the I-III-VI group compound may be CuInSe 2 、CuInS 2 , CuInGaSe, and CuInGaS, but not limited thereto. Examples of the I-II-IV-VI group compound may be CuZnSnSe and CuZnSnS, but not limited thereto. Examples of the IV group element or compound may be a simple substance selected from Si, Ge, and a mixture thereof; and a binary compound selected from SiC, SiGe, and a mixture thereof.

[0135] The binary compound, the ternary compound, or the quaternary compound is present in a particle at a uniform concentration or in the same particle at a locally different concentration.

[0136] According to one embodiment, the quantum dot may have a core-shell structure comprising a semiconductor nanocrystal core particle and another semiconductor nanocrystal shell around the core. The core and the shell may have a concentration gradient in which the concentration of the element of the shell decreases toward the core. In addition, the quantum dot may have a semiconductor nanocrystal core and a multilayer shell around the core. Here, the multilayer shell structure has a structure of two or more shells and each layer may have a single composition or alloy or may have a concentration gradient.

[0137] When the quantum dot has a core-shell structure, the material composition of the shell has a larger band gap than the material composition of the core, which can present an effective quantum confinement effect. However, the embodiment is not limited thereto. At the same time, in the multi-layer shell, the shell farthest from the core may have a higher band gap than the shell closest to the core and the quantum dot may emit light in the ultraviolet (UV) to infrared wavelength range.

[0138] The quantum dots may have a quantum efficiency of greater than or equal to about 10%, for example, greater than or equal to about 20%, greater than or equal to about 30%, greater than or equal to about 40%, greater than or equal to about 50%, greater than or equal to about 60%, greater than or equal to about 70%, greater than or equal to about 90%, or even 100%.

[0139] In a display device, the quantum dots may have a relatively narrow spectrum to improve color purity or color reproducibility. The quantum dots may have, for example, a half width (FWHM) of a photoluminescence wavelength spectrum of less than or equal to about 45 nm, less than or equal to about 40 nm, or less than or equal to or about 30 nm. Within the range, the color purity or color reproducibility of the device may be improved.

[0140] The quantum dots may have a particle diameter of about 1 nm to about 100 nm (the longest dimension for non-spherical particles). For example, the quantum dots may have a particle diameter of about 1 nm to about 20 nm, such as about 2 nm (or about 3 nm) to about 15 nm.

[0141] In addition, the shape of the quantum dot can be a common shape in the art and therefore may not be particularly limited. For example, the quantum dot may have a spherical, elliptical, tetrahedral, pyramidal, cuboctahedral, cylindrical, polyhedral, multi-armed, or cubic nanoparticle, nanotube, nanowire, nanofiber, nanosheet, or a combination thereof. The quantum dot may have any cross-sectional shape.

[0142] The quantum dots may be commercially available or may be synthesized by any method. For example, several (several) nanometer-sized quantum dots may be synthesized according to a wet chemical process. In the wet chemical process, a precursor is reacted in an organic solvent to grow crystalline particles, and the organic solvent or ligand compound may coordinate to the surface of the quantum dots, thereby controlling the growth of the crystal. Examples of the organic solvent and the ligand compound are known.

[0143] The organic material coordinated on the surface of the quantum dots may affect the stability of the device, and therefore the excess organic material not coordinated on the surface of the quantum dots may be removed by pouring it into an excess of a non-solvent and centrifuging the resulting mixture. Examples of the non-solvent may be acetone, ethanol, methanol, etc., but are not limited thereto. After removing the excess organic material, the amount of organic material coordinated on the surface of the quantum dots may be less than or equal to about 50 wt %, for example, less than or equal to about 30 wt %, less than or equal to about 20 wt %, or less than or equal to about 10 wt %, based on the weight of the quantum dots. The organic material may include a ligand compound, an organic solvent, or a combination thereof.

[0144] The electroluminescent device 10 according to the embodiment may further include a ligand having a hydrophobic portion (hereinafter, referred to as a hydrophobic ligand) that binds to the surface of the quantum dot 141. In one embodiment, the hydrophobic ligand may include a functional group that binds to the surface of the quantum dot 141 and a hydrophobic functional group that provides hydrophobicity.

[0145] The hydrophobic portion may be, for example, a C4-C20 alkyl group, a C4-C20 alkenyl group, a C4-C20 alkynyl group, or a combination thereof and the functional group bound to the surface of the quantum dot 141 may be, for example, a hydroxyl group (-OH), a carboxyl group (-COOH), or the like.

[0146] Examples of the hydrophobic ligands may be fatty acids such as oleic acid, stearic acid, palmitic acid, etc. When the hydrophobic ligands as described are included, the quantum dots 141 may exhibit non-polarity as a whole, and the emission layer 140 including the same may exhibit non-polarity as a whole. The quantum dots 141 with attached hydrophobic ligands may have solvent selectivity for non-polar solvents, particularly aliphatic non-polar solvents, that is, may be dissolved therein.

[0147] In the electroluminescent device 10 according to the embodiment, the emission layer 140 may include the quantum dots 141 in an appropriate amount to exhibit excellent light emission efficiency.

[0148] For example, based on 100 wt % of the emission layer, quantum dots 141 may be included in an amount, for example, greater than or equal to about 5 wt %, greater than or equal to about 10 wt %, greater than or equal to about 15 wt %, or greater than or equal to about 20 wt % and less than or equal to about 98 wt %, less than or equal to about 95 wt %, less than or equal to about 90 wt %, less than or equal to about 85 wt %, less than or equal to about 80 wt %, less than or equal to about 75 wt %, less than or equal to about 70 wt %, less than or equal to about 65 wt %, less than or equal to about 60 wt %, less than or equal to about 55 wt %, or less than or equal to about 50 wt %, for example, from about 5 wt % to about 98 wt %, from about 20 wt % to about 98 wt %, from about 20 wt % to about 90 wt %, from about 20 wt % to about 85 wt %, or from about 50 wt % to about 85 wt %.

[0149] However, the embodiment is not limited thereto, and the amount of quantum dots 141 may vary depending on the material of the quantum dots 141 used, the type of light emitted, the amount of the hydrophobic ligand used, and the thickness of the hole transport layer 130, the emission layer 140 and / or the electron transport layer 150.

[0150] On the other hand, the first hole transport material can improve the hole transport ability of the emission layer 140. The first hole transport material may be a material different from the second hole transport material of the hole transport layer 130. The first hole transport material may be a p-type semiconductor material, or a material doped with a p-type dopant and may be selected from a single molecule to a low molecule material, or a combination thereof, which is different from the second hole transport material.

[0151] In one embodiment, the first hole transport material having a substituted or unsubstituted C4-C20 alkyl group attached to the backbone structure may be soluble in a non-polar solvent, particularly an aliphatic non-polar solvent. In one embodiment, both the first hole transport material and the hydrophobic ligand may be soluble in an aliphatic non-polar solvent. Therefore, when the emission layer 140 is formed using the solution, the formed emission layer 140 may have an improved surface morphology. Moreover, due to the first hole transport material, the formed emission layer 140 may have excellent hole transport capability.

[0152] As described, the emission layer 140 and the hole transport layer 130 have solubility in the aliphatic nonpolar solvent and the aromatic nonpolar solvent, respectively, and thus damage to the surface of the hole transport layer 130 can be minimized during the formation of the emission layer 140 and thus the hole transport layer 130 can maintain excellent hole transporting ability.

[0153] In one embodiment, the first hole transport material may have a substituted or unsubstituted C4-C20 alkyl group attached to the backbone structure. When the first hole transport material has a substituted or unsubstituted C4-C20 alkyl group attached to the backbone structure, the first hole transport material may be dissolved in a non-polar solvent, particularly an aliphatic non-polar solvent.

[0154] In one embodiment, the first hole transport material may be a compound represented by Chemical Formula 1.

[0155] [Chemical formula 1]

[0156]

[0157] In Chemical Formula 1,

[0158] R 1 -R 8 independently selected from substituted or unsubstituted C4-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C3-C20 heteroaryl, substituted or unsubstituted C1-C20 alkylamine, substituted or unsubstituted C4-C20 arylamine, and substituted or unsubstituted carbazolyl, with the proviso that R 1 -R 8 At least one of is a substituted or unsubstituted C4-C20 alkyl group,

[0159] When R 3 -R 8 When it is a substituted or unsubstituted C3-C20 cycloalkyl group, a substituted or unsubstituted C6-C20 aryl group, or a substituted or unsubstituted C3-C20 heteroaryl group, they are fused with the adjacent aromatic ring to provide a C8-C40 fused ring,

[0160] X 1 and X 2 are independently selected from N and C(-R a ), and X 3 and X 4 Independently selected from S, NR b , and C(-R c )(-R d )(where R a , R b , R c , and R d independently selected from substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, substituted or unsubstituted C6-C20 aryl, and substituted or unsubstituted C3-C20 heteroaryl),

[0161] L 1 and L 2 are independently selected from a single bond and a substituted or unsubstituted methylene or C2-C4 alkenylene, and

[0162] i, j, k, l, and m are independently 0 or 1. When i, j, k, l, or m is 0, the corresponding part represented by it does not exist. For example, when j is 0, for and when i is 0, for

[0163] Since the first hole transport material includes a compound having a relatively small molecular weight as shown in Chemical Formula 1 and is well mixed with the ligand on the surface of the quantum dots, the emission layer 140 can present an improved surface morphology compared to when including quantum dots alone and / or including quantum dots and polymer / oligomer hole transport materials.

[0164] Particularly, the first hole transport material may include a compound represented by Chemical Formula 2.

[0165] [Chemical formula 2]

[0166]

[0167] Wherein, in Chemical Formula 2,

[0168] X 3 , X 4 , L 1 , L 2 , j, k, l, and m are the same as those defined in Chemical Formula 1,

[0169] R 1 -R 8independently selected from substituted or unsubstituted C4-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C3-C20 heteroaryl, substituted or unsubstituted C1-C20 alkylamine, substituted or unsubstituted C4-C20 arylamine, and substituted or unsubstituted carbazolyl, with the proviso that R 1 -R 6 At least one of is a substituted or unsubstituted C4-C20 alkyl group, and

[0170] When R 3 -R 6 When it is one of a substituted or unsubstituted C3-C20 cycloalkyl group, a substituted or unsubstituted C6-C20 aryl group, or a substituted or unsubstituted C3-C20 heteroaryl group, they are condensed with the adjacent aromatic ring to provide a C8-C40 condensed ring.

[0171] In chemical formula 2, R 1 -R 6 At least two of may be substituted or unsubstituted C4-C20 alkyl groups. In this case, the solubility of the first hole transport material in the aliphatic non-polar solvent may be further improved.

[0172] For example, the first hole transport material may include at least one of the compounds represented by Chemical Formula 2-1 to Chemical Formula 2-2.

[0173] [Chemical formula 2-1]

[0174]

[0175] [Chemical formula 2-2]

[0176]

[0177] In Chemical Formula 2-1 to Chemical Formula 2-2,

[0178] X 3 and X 4 Same as defined in Chemical Formula 1,

[0179] R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 21 , R 22 , R 23 , R 24 , R 25 , and R 26are independently selected from substituted or unsubstituted C4-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, substituted or unsubstituted C6-C20 aryl, and substituted or unsubstituted C3-C20 heteroaryl, with the proviso that R 11 -R 14 At least one and R 21 -R 26 At least one of is a substituted or unsubstituted C4-C20 alkyl group,

[0180] R 27 and R 28 independently selected from substituted or unsubstituted C1-C20 alkylamine groups, substituted or unsubstituted C4-C20 arylamine groups, and substituted or unsubstituted carbazolyl groups, and

[0181] When R 13 , R 14 , R 15 、R1 6 , R 23 , R 24 , R 25 , and R 26 When it is one of a substituted or unsubstituted C3-C20 cycloalkyl group, a substituted or unsubstituted C6-C20 aryl group, or a substituted or unsubstituted C3-C20 heteroaryl group, they are condensed with the adjacent aromatic ring to provide a C8-C40 condensed ring.

[0182] On the other hand, the first hole transport material may include a compound represented by Chemical Formula 3.

[0183] [Chemical formula 3]

[0184]

[0185] In chemical formula 3,

[0186] X 3 , X 4 , L 1 , L 2 , j, k, l, and m are independently the same as defined in Formula 1, and

[0187] R 33 , R 34 , R 35 , R 36 , R 37 , and R 38independently selected from substituted or unsubstituted C4-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C3-C20 heteroaryl, substituted or unsubstituted C1-C20 alkylamine, substituted or unsubstituted C4-C20 arylamine, and substituted or unsubstituted carbazolyl, with the proviso that R 33 -R 38 At least one of is a substituted or unsubstituted C4-C20 alkyl group, and

[0188] When R 33 , R 34 , R 35 , R 36 , R 37 , and R 38 When it is one of a substituted or unsubstituted C3-C20 cycloalkyl group, a substituted or unsubstituted C6-C20 aryl group, or a substituted or unsubstituted C3-C20 heteroaryl group, they are condensed with the adjacent aromatic ring to provide a C8-C40 condensed ring.

[0189] In chemical formula 3, R 33 -R 36 At least two of the may be unsubstituted C4-C10 straight chain or branched alkyl groups. In this case, the solubility of the first hole transport material in the aliphatic non-polar solvent may be further improved.

[0190] More specifically, the first hole transport material may include at least one of the compounds represented by Chemical Formula A to Chemical Formula F.

[0191] [Chemical formula A]

[0192]

[0193] [Chemical formula B]

[0194]

[0195] [Chemical formula C]

[0196]

[0197] [Chemical formula D]

[0198]

[0199] [Chemical formula E]

[0200]

[0201] [Chemical formula F]

[0202]

[0203] Hole transport materials widely used in electroluminescent devices using quantum dots have slower hole mobility than electron transport materials. In order to ensure stability, such as the lifetime of quantum dots, organic ligands are bound to the surface of quantum dots, and the organic ligands attached to the surface of quantum dots generally have very low hole mobility.

[0204] Therefore, when the electroluminescent device is driven, electrons and holes may not meet each other at the center of the emission layer, but at the interface between the emission layer and the hole transport layer or at the hole transport layer. In this case, there is a possibility that the quantum efficiency of the light-emitting layer is significantly reduced, and therefore, the electron / hole carrier balance in the electroluminescent device must be set to an appropriate level.

[0205] Therefore, a method of forming an emission layer by blending quantum dots with conventional hole transport materials has been considered. However, since conventional hole transport materials generally use high molecular weight materials such as polymers / oligomers, when they are blended with quantum dots, the surface morphology may be formed unevenly. If the surface morphology of the emission layer is uneven, many cracks, holes, etc. may be generated on the surface of the emission layer. Since the cracks and / or holes act as leakage paths for holes and electrons, when the surface morphology becomes uneven, the leakage current and the on-voltage may increase and the life of the device may be greatly deteriorated.

[0206] Furthermore, when a composition obtained by blending quantum dots with a conventional hole transport material is spin-coated, the composition may not be formed into a uniform thin film and may be pushed out, so that an emission layer may not be formed.

[0207] On the other hand, the electroluminescent device 10 according to the embodiment includes the emission layer 140 including the quantum dots 141 bound to the hydrophobic ligand and the first hole transport material of single molecule to low molecule represented by Chemical Formula 1.

[0208] As described above, compared with a blend of a conventional hole transport material and quantum dots, the emission layer 140 composed of a blend of quantum dots 141 and the first single-molecule to low-molecule hole transport material has a better surface morphology. Therefore, cracks and / or holes on the surface of the emission layer are minimized, thereby reducing leakage current and on-voltage, and significantly improving the life of the device.

[0209] In addition, the emission layer 140 composed of the quantum dots 141 and the single-molecule to low-molecule first hole transport material can be obtained as a uniform thin film that is easily formed by using a solution process such as spin coating.

[0210] Meanwhile, the electroluminescent device 10 according to the embodiment can be designed so that the emission layer 140 and the hole transport layer 130 have relatively different solvent selectivities. Therefore, damage to the surface of the hole transport layer 130 can be minimized during the formation of the emission layer 140, which further reduces leakage current and on-voltage.

[0211] In addition, since the first hole transport material is included in the emission layer 140, the hole injection into the emission layer 140 is promoted, so that the conduction of the electroluminescent device 10 can be accelerated, the hole carriers injected into the emission layer 140 can be easily adjusted, and the electric field voltage applied to the emission layer 140 can be reduced to improve the luminous efficiency, maximum brightness and lifespan.

[0212] The amount of the first hole transport material in the emission layer 140 may be controlled according to the degree of hole / electron transporting ability of the hole transport layer 130 and the electron transport layer 150 to effectively control the hole / electron carrier balance in the emission layer 140. For example, based on 100 wt% of the total weight of the emission layer 140, the first hole transport material may be included in an amount of, for example, greater than or equal to about 2 wt%, greater than or equal to about 5 wt%, or greater than or equal to about 10 wt% and, for example, less than about 50 wt%, for example, less than or equal to about 49 wt%, less than or equal to about 45 wt%, less than or equal to about 40 wt%, less than or equal to about 30 wt%, or, for example, greater than or equal to about 2 wt% and less than about 50 wt%, for example, greater than or equal to about 5 wt% and less than about 50 wt%, about 5 wt% to about 40 wt%, about 5 wt% to about 30 wt%, or about 5 wt% to about 20 wt%.

[0213] When the first hole transport material is included in the emission layer 140 in an amount within the above range, overall light emitting efficiency and lifespan characteristics of the electroluminescent device 10 may be greatly improved.

[0214] The surface morphology of the emission layer 140 according to the embodiment can be confirmed by using atomic force microscopy (AFM). In one embodiment, the root mean square roughness of the emission layer 140 measured by atomic force microscopy (AFM) may be, for example, greater than or equal to about 0.1, greater than or equal to about 0.2, greater than or equal to about 0.3, greater than or equal to about 0.4, greater than or equal to about 0.5, greater than or equal to about 0.6, greater than or equal to about 0.7, greater than or equal to about 0.8, or greater than or equal to about 0.9 and, for example, less than or equal to about 2.0, or less than or equal to about 1.5, or, for example, about 0.5-about 2.0, or about 0.8-about 1.5.

[0215] That is, when the emission layer 140 in the electroluminescent device 10 according to the embodiment is formed by blending the quantum dots 141 and the first hole transport material, the emission layer 140 may have excellent surface morphology as described above.

[0216] However, the method for confirming the surface morphology of the emission layer 140 in the electroluminescent device 10 according to the embodiment is not limited to the above-mentioned measurement method. For example, for the emission layer including the quantum dots and the hole transport material, the surface morphology can be measured by using other measurement methods such as Zygo interferometer. In this case, a root mean square roughness range different from the above can be obtained. However, if the root mean square roughness measured by the measurement method according to the embodiment satisfies the above range, the emission layer falls within the scope of the present disclosure.

[0217] In one embodiment, the thickness of the emission layer 140 may be variously selected in consideration of the respective materials, respective electron / hole mobilities, and respective thicknesses of the hole transport layer 130 and the electron transport layer 150, but may have an average thickness of, for example, about 15 nm to about 100 nm, about 20 nm to about 60 nm, about 20 nm to about 50 nm, about 20 nm to about 40 nm, or about 25 nm to about 30 nm.

[0218] When the thickness of the emission layer 140 is less than 15 nm, voids, cracks, etc. present in the emission layer 140 tend to act as leakage paths for electrons / holes, greatly deteriorating device characteristics, and it may be difficult to match carrier balance with other constituent elements of the electroluminescent device.

[0219] On the other hand, when the thickness of the emission layer 140 is greater than 100 nm, it is difficult to match the electron / hole carrier balance and the current and voltage conditions required for driving become too high, thereby making it difficult to achieve efficient light emission.

[0220] That is, when the thickness range of the emission layer 140 is outside the above range, electrons may be supplied to the emission layer 140 too quickly and / or in too large an amount compared to holes, and thus the electrons may combine with holes at the interface between the emission layer 140 and the hole transport layer 130 to cause interfacial light emission or may be transported to the hole injection layer 120 and the hole transport layer 130 and then may be quenched.

[0221] However, the thickness of the emission layer 140 according to the embodiment may be variously adjusted in consideration of the relationship with the materials and thicknesses of other components. For example, considering the luminous efficiency of the emission layer 140, the thickness of the emission layer 140 may be less than or equal to about 60 nm to minimize the field-induced quenching caused by the electric field by reducing the on-voltage and electric field of the emission layer.

[0222] The electroluminescent device 10 according to the embodiment improves the transport capability of the emission layer 140 and improves the hole transport / injection capability by including the first hole transport material in the emission layer 140 of the device. As a result, it is easy to match the hole / electron carrier balance in the device.

[0223] The electron transport layer 150 is disposed between the emission layer 140 and the second electrode 160 and thus transports electrons into the emission layer 140 .

[0224] In one embodiment, the thickness of the electron transport layer 150 may vary depending on the charge carrier balance of the hole injection layer 120, the hole transport layer 130, and / or the emission layer 140 in the device, but may be, for example, greater than or equal to about 20 nm, greater than or equal to about 30 nm, greater than or equal to about 40 nm, or greater than or equal to about 50 nm and, for example, less than or equal to about 100 nm, less than or equal to about 90 nm, less than or equal to about 80 nm, less than or equal to about 70 nm, or less than or equal to about 60 nm, for example, about 20 nm-about 100 nm, about 20 nm-about 90 nm, about 30 nm-about 80 nm, about 40 nm-about 80 nm, or about 60 nm-about 80 nm.

[0225] When the electron transport layer 150 has a thickness outside the range, voids, cracks, etc. of the electron transport layer 150 may have a large impact on the electron transport capability, thereby greatly reducing device characteristics, and it is difficult to satisfy the carrier balance with other constituent elements of the electroluminescent device.

[0226] In one embodiment, the electron transport layer 150 may be composed of a non-luminescent electron transport material that does not emit light by an electric field so that electrons may not be quenched internally.

[0227] On the other hand, the electron transport layer 150 may include inorganic material nanoparticles or may be an organic layer formed by deposition. For example, the electron transport layer 150 may include inorganic material nanoparticles, quinolone-based compounds, triazine-based compounds, quinoline-based compounds, triazole-based compounds, naphthalene-based compounds, or a combination thereof.

[0228] In one embodiment, the electron transport layer 150 may include inorganic material nanoparticles. The inorganic material nanoparticles impart electron transport properties to the electron transport layer 150 and do not exhibit luminescent properties. In one embodiment, the electron transport layer 150 may include at least two inorganic material nanoparticles. In one embodiment, the electron transport layer 150 may include a cluster layer formed of at least two inorganic material nanoparticles.

[0229] On the other hand, an electron injection layer that facilitates injection of electrons may be further provided between the electron transport layer 150 and the second electrode 160 and / or a hole blocking layer that blocks movement of holes may be further provided between the electron transport layer 150 and the emission layer 140 .

[0230] The electron injection layer and the hole blocking layer may have respective thicknesses selected as desired. For example, each thickness may be within a range of greater than or equal to about 1 nm and less than or equal to about 500 nm, but is not limited thereto. The electron injection layer may be an organic layer formed by deposition.

[0231] The electron injection layer may include, for example, 1,4,5,8-naphthalene-tetracarboxylic dianhydride (NTCDA), bathocuproin (BCP), tris[3-(3-pyridyl)- yl]borane (3TPYMB), LiF, Alq 3 , Gaq 3 、Inq 3 、Znq 2 、Zn(BTZ) 2 、BeBq 2 , ET204 (8-(4-(4,6-di(naphthalene-2-yl)-1,3,5-triazine-2-yl)phenyl)quinolone), 8-hydroxyquinoline lithium (Liq), n-type metal oxides (such as ZnO, HfO 2 etc.), ET204 (8-(4-(4,6-di(naphthalene-2-yl)-1,3,5-triazine-2-yl)phenyl)quinolone), Bphen, ABH113, NET218, NET338, NDN77, NDN87, and at least one of their combinations, but not limited thereto.

[0232] The hole blocking layer (HBL) may include, for example, 1,4,5,8-naphthalene-tetracarboxylic dianhydride (NTCDA), bathocuproine (BCP), tris[3-(3-pyridyl)- yl]borane (3TPYMB), LiF, Alq 3 , Gaq 3 、Inq 3 、Znq 2 、Zn(BTZ) 2 、BeBq 2 , and at least one of a combination thereof, but not limited thereto.

[0233] As described above, the electroluminescent device 10 according to the embodiment can improve the hole mobility of the emission layer 140 by including the quantum dots and the first hole transport material in the emission layer 140. In addition, the first hole transport material in the emission layer is a monomolecular to low-molecular material having a substituted or unsubstituted C4-C20 alkyl group connected to a backbone structure, and thus the solubility in a non-polar solvent is improved and when the light-emitting layer including the quantum dots and the first hole transport material is formed using a solution process, the formed emission layer can have an improved surface morphology.

[0234] In addition, according to an embodiment, the emission layer 140 and the hole transport layer 130 may be controlled to have solvent selectivity as described above. Therefore, since the surface of the hole transport layer 130 is not damaged, the emission layer 140 and the hole transport layer 130 may maintain excellent hole transport capabilities.

[0235] In addition, since the first hole transport material included in the emission layer 140 has a substituted or unsubstituted C4-C20 alkyl group connected to the backbone structure, it can be dissolved in the aliphatic non-polar solvent together with the quantum dots to which the hydrophobic ligands are attached. Therefore, when the emission layer 140 is formed using the solution, the surface morphology of the formed emission layer 140 is improved. Moreover, due to the first hole transport material, the hole transport capacity is improved. As a result, since the hole transport capacity of the emission layer 140 itself is improved and the conductivity of the emission layer 140 is also improved, the quenching of the emission layer 140 caused by the electric field can be reduced and thus the luminous efficiency, brightness, and life of the electroluminescent device 10 can be greatly improved.

[0236] Hereinafter, a display device including the electroluminescent device 10 is described.

[0237] A display device according to an embodiment includes a substrate, a driving circuit formed on the substrate, and a first electroluminescent device, a second electroluminescent device, and a third electroluminescent device disposed on the driving circuit and spaced apart from each other at predetermined intervals.

[0238] The first to third electroluminescent devices have the same structure as the electroluminescent device 10, but the wavelengths of light emitted from quantum dots of the respective electroluminescent devices may be different from each other.

[0239] In one embodiment, the first electroluminescent device is a red device that emits red light, the second electroluminescent device is a green device that emits green light, and the third electroluminescent device is a blue device that emits blue light. In other words, the first to third electroluminescent devices may be pixels that express (display) red, green, and blue, respectively, in the display device.

[0240] However, the embodiment is not necessarily limited thereto, but the first to third electroluminescent devices may express magenta, yellow, and cyan, respectively, or may express other colors.

[0241] One of the first to third electroluminescent devices may be the electroluminescent device 10. In this case, the third electroluminescent device showing at least blue may be the electroluminescent device 10 desirably.

[0242] In a display device according to an embodiment, the hole injection layer, hole transport layer, electron transport layer, electron injection layer, and hole blocking layer of each pixel other than the emission layer may be integrated to form a common layer. However, the embodiment is not limited thereto. A hole injection layer, a hole transport layer, an electron transport layer, an electron injection layer, and a hole blocking layer may be independently formed in each pixel of the display device, or at least one of the hole injection layer, the hole transport layer, the electron transport layer, the electron injection layer, and the hole blocking layer may form a common layer and the remaining layers may form separate independent layers.

[0243] The substrate may be a transparent insulating substrate or may be made of a ductile material. The substrate may include glass or a polymer material in the form of a film having a glass transition temperature (Tg) greater than about 150°C. For example, it includes a material based on COC (cyclic olefin copolymer) or COP (cyclic olefin polymer). All of the first to third electroluminescent devices are formed on the substrate. That is, the substrate of the display device according to the embodiment provides a common layer.

[0244] The driving circuit is disposed on the substrate and is independently connected to each of the first to third electroluminescent devices. The driving circuit may include at least one line including a scan line, a data line, a driving power line, a common power line, etc., at least two thin film transistors (TFTs) connected to the line and corresponding to one organic light emitting diode, and at least one capacitor, etc. The driving circuit may have a variety of known structures.

[0245] As described above, the display device according to the embodiment may exhibit improved device efficiency and thus excellent photoluminescence characteristics.

[0246] Hereinafter, the embodiments are described in more detail with reference to Examples. However, these Examples are exemplary, and the present disclosure is not limited thereto.

[0247] Preparation Example 1

[0248] 5×10 red quantum dots (InP, average particle diameter: 9 nm) to which oleic acid was attached as a hydrophobic ligand -5mmol and 2.66 mmol of the compound represented by Chemical Formula D (DOFL-TPD) were placed in 10 mL of octane and stirred for 5 minutes, thereby preparing a composition for an emission layer.

[0249] The compound represented by Chemical Formula D is included in an amount of 5 wt % based on the total weight of the quantum dots and the compound represented by Chemical Formula D.

[0250] Preparation Example 2

[0251] A composition for an emission layer was prepared according to the same method as Preparation Example 1, except that the amount of the compound represented by Chemical Formula D was adjusted to 10 wt % based on the total weight of the quantum dots and the compound represented by Chemical Formula D.

[0252] Preparation Example 3

[0253] A composition for an emission layer was prepared according to the same method as Preparation Example 1, except that the amount of the compound represented by Chemical Formula D was adjusted to 15 wt % based on the total weight of the quantum dots and the compound represented by Chemical Formula D.

[0254] Preparation Example 4

[0255] A composition for an emission layer was prepared according to the same method as Preparation Example 1, except that the amount of the compound represented by Chemical Formula D was adjusted to 20 wt % based on the total weight of the quantum dots and the compound represented by Chemical Formula D.

[0256] Preparation Example 5

[0257] Blue quantum dots (ZnSeTe, average particle diameter: 13 nm) to which oleic acid was attached as a hydrophobic ligand 3.33 × 10 -5 mmol and 2.66 mmol of the compound represented by Chemical Formula D (DOFL-TPD) were placed in 10 mL of octane and stirred for 5 minutes, thereby preparing a composition for an emission layer.

[0258] The compound represented by Chemical Formula D was included in an amount of 15 wt % based on the total weight of the quantum dot and the compound represented by Chemical Formula D.

[0259] Preparation Example 6

[0260] A composition for an emission layer was prepared according to the same method as in Preparation Example 1, except that 3.64 mmol of the compound represented by Chemical Formula B (DOFL-NPB) was used instead of the compound represented by Chemical Formula D (DOFL-TPD), and the amount of the compound represented by Chemical Formula B was adjusted to 5 wt %, based on the total weight of the quantum dots and the compound represented by Chemical Formula B.

[0261] Preparation Example 7

[0262] A composition for an emission layer was prepared according to the same method as Preparation Example 6, except that the amount of the compound represented by Chemical Formula B was adjusted to 10 wt % based on the total weight of the quantum dots and the compound represented by Chemical Formula B.

[0263] Preparation Example 8

[0264] A composition for an emission layer was prepared according to the same method as Preparation Example 6, except that the amount of the compound represented by Chemical Formula B was adjusted to 15 wt % based on the total weight of the quantum dots and the compound represented by Chemical Formula B.

[0265] Preparation Example 9

[0266] A composition for an emission layer was prepared according to the same method as Preparation Example 6, except that the amount of the compound represented by Chemical Formula B was adjusted to 20 wt % based on the total weight of the quantum dots and the compound represented by Chemical Formula B.

[0267] Preparation Example 10

[0268] A composition for an emission layer was prepared according to the same method as Preparation Example 1, except that the amount of the compound represented by Chemical Formula D was adjusted to 30 wt % based on the total weight of the quantum dots and the compound represented by Chemical Formula D.

[0269] Preparation Example 11

[0270] A composition for an emission layer was prepared according to the same method as Preparation Example 6, except that the amount of the compound represented by Chemical Formula B was adjusted to 40 wt % based on the total weight of the quantum dots and the compound represented by Chemical Formula B.

[0271] Preparation Comparative Example 1

[0272] 5×10 red quantum dots (InP, average particle diameter: 9 nm) to which oleic acid was attached as a hydrophobic ligand -5mmol was placed in 10 mL of octane and stirred for 5 minutes, thereby preparing a composition for an emission layer.

[0273] Preparation Comparative Example 2

[0274] Blue quantum dots (ZnSeTe, average particle diameter: 13 nm) to which oleic acid was attached as a hydrophobic ligand 3.33 × 10 -5 mmol was added to 10 mL of octane and stirred for 5 minutes, thereby preparing a composition for an emission layer.

[0275] Preparation Comparative Example 3

[0276] A composition for an emission layer was prepared according to the same method as Preparation Example 6, except that the amount of the compound represented by Chemical Formula B was adjusted to 50 wt % based on the total weight of the quantum dots and the compound represented by Chemical Formula B.

[0277] Preparation Comparative Example 4

[0278] A composition for an emission layer was prepared according to the same method as Preparation Example 1, except that the amount of the compound represented by Chemical Formula D was adjusted to 50 wt % based on the total weight of the quantum dots and the compound represented by Chemical Formula D.

[0279] Evaluation 1: Surface morphology of the emission layer

[0280] The compositions for the emission layer according to Preparation Examples 3 and 5 and Preparation Comparative Examples 1 and 2 were spin-coated on glass substrates, respectively, and heat-treated at 80° C. for 30 minutes to form each emission layer thin film having an average thickness of about 25 nm.

[0281] Subsequently, the surface morphology of each emission layer film was measured by atomic force microscopy (AFM), and the results are shown in Figure 2-5 middle.

[0282] Figure 2-5 To show the surface morphology of the emission layer film, an atomic force microscope (AFM) image (Comparative Example 1 ( Figure 2 ), Preparation Example 3 ( Figure 3 ), Preparation Comparative Example 2 ( Figure 4 ), and Preparation Example 5 ( Figure 5 )).

[0283] exist Figure 2-5 , each image has each width dimension corresponding to 5 μm, and here, when the image shows a brighter color, it is located at a relatively upper portion, but when it shows a darker color, it is located at a relatively lower portion.

[0284] refer to Figure 2-5 , the emission layer thin films based on the same kind of quantum dots according to Preparation Examples 3 and 5 in which a hole transport material is blended show lower root mean square roughness (RMS) than those according to Preparation Comparative Examples 1 and 2 which do not include a hole transport material.

[0285] Figure 2-5 The results show that the emission layer formed by blending the hole transport material with the quantum dots according to the embodiment shows excellent surface morphology compared to the emission layer including only the quantum dots.

[0286] Evaluation 2: Evaluation of the hole transport capability of HOD

[0287] HOD (single hole device) was manufactured using the compositions for emission layer according to Preparation Examples 2-3 and 6-8 and Preparation Comparative Example 1, respectively. HOD can be manufactured by spin-coating a solution for hole injection layer prepared by dissolving PEDOT in water and a solution for hole transport layer prepared by dissolving TFB in toluene on a patterned ITO electrode to sequentially form a hole injection layer and a hole transport layer, respectively, coating and drying the composition for emission layer thereon to form an emission layer, depositing a material that blocks holes from passing through the emission layer on the emission layer, and finally forming an Al electrode. The manufactured HOD can effectively detect only hole transport capability.

[0288] Subsequently, the current density measured in each emission layer after applying voltages of 5 V and 8 V to the HOD is shown in Table 1.

[0289] (Table 1)

[0290]

[0291] Referring to Table 1, the HOD manufactured by using the composition for an emission layer according to Preparation Example showed improved current density compared to the HOD manufactured by using the composition for an emission layer according to Comparative Preparation Example 1.

[0292] On the other hand, when the same kind of hole transport material was used (Comparison of Preparation Examples 2 and 3 and Comparison of Preparation Examples 6 to 8), as the amount of the hole transport material increased, the current density also increased.

[0293] However, when different kinds of hole transport materials are used (comparison of Preparation Examples 2-3 and Preparation Examples 6-8), the current density also becomes different.

[0294] Referring to the results of Table 1, the HOD according to the Preparation Example shows a greatly improved hole transport capability through the emission layer formed by blending the quantum dots and the hole transport material.

[0295] Evaluation 3: Surface properties of the emission layer depending on the content of the first hole transport material

[0296] The compositions for the emission layer according to Preparation Examples 10-11 and Preparation Comparative Examples 3-4 were coated and dried on glass substrates to form emission layer films, respectively. The surface of each emission layer film was measured by using a scanning electron microscope, and the results are shown in Figure 6-9 middle.

[0297] Figure 6-9 is a scanning electron microscope image of the emission layer film (Comparative Example 3 ( Figure 6 ), Preparation Comparative Example 4 ( Figure 7 ), Preparation Example 10 ( Figure 8 ), and Preparation Example 11 ( Fig. 9 )).

[0298] refer to Figure 6-9 , the emission layers according to Preparation Examples 10-11 show a relatively uniform surface distribution, but when the first hole transport material is included in an excessive amount, phase separation may occur as shown in Comparative Preparation Examples 3-4.

[0299] Therefore, referring to the results of Evaluation 3, the electroluminescent device according to the embodiment includes the first hole transport material in the emission layer within the above range and thus can prevent phase separation on the surface of the emission layer and secure excellent surface roughness.

[0300] Example 1

[0301] A glass substrate on which ITO was deposited as the first electrode (anode) was surface treated with UV-ozone for 15 minutes, and a hole injection layer having an average thickness of 30 nm was formed thereon by spin coating a PEDOT:PSS solution (HC Starks) and heat treating it at 150° C. for 10 minutes in an air atmosphere, and then 2 The film was heat treated at 150° C. for 10 minutes in an aqueous solution.

[0302] Subsequently, a hole transport layer having an average thickness of 25 nm was formed on the hole injection layer by spin coating a solution for a hole transport layer prepared by dissolving poly[(9,9-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-4-butylphenyl)diphenylamine)] (TFB) (Sumitomo) in toluene, and heat treating it at 150° C. for 30 minutes.

[0303] Subsequently, the composition for an emission layer according to Preparation Example 1 was spin-coated on the hole transport layer and heated at 80° C. to form a red emission layer (a layer emitting red light) having an average thickness of 25 nm.

[0304] On the red emission layer, an electron transport layer having an average thickness of 80 nm was formed by spin coating a solution for an electron transport layer in which ZnO was dispersed in ethanol and then heat-treating it at 80° C. for 30 minutes.

[0305] Subsequently, the electroluminescent device according to Example 1 was manufactured by forming a second electrode by vacuum-depositing aluminum (Al) to a thickness of 90 nm on the electron transport layer.

[0306] Example 2

[0307] The electroluminescent device according to Example 2 was manufactured according to the same method as Example 1, except that the composition for an emission layer according to Preparation Example 2 was used instead of the composition for an emission layer according to Preparation Example 1.

[0308] Example 3

[0309] The electroluminescent device according to Example 3 was manufactured according to the same method as Example 1, except that the composition for an emission layer according to Preparation Example 3 was used instead of the composition for an emission layer according to Preparation Example 1.

[0310] Example 4

[0311] The electroluminescent device according to Example 4 was manufactured according to the same method as Example 1, except that the composition for an emission layer according to Preparation Example 4 was used instead of the composition for an emission layer according to Preparation Example 1.

[0312] Example 5

[0313] The electroluminescent device according to Example 5 was manufactured according to the same method as Example 1, except that the composition for emission layer according to Preparation Example 2 was used instead of the composition for emission layer according to Preparation Example 1 and the electron transport layer was formed with an average thickness of 60 nm.

[0314] Example 6

[0315] The electroluminescent device according to Example 6 was manufactured according to the same method as Example 1, except that the composition for emission layer according to Preparation Example 3 was used instead of the composition for emission layer according to Preparation Example 1 and the electron transport layer was formed with an average thickness of 60 nm.

[0316] Example 7

[0317] An electroluminescent device according to Example 7 was manufactured according to the same method as Example 1, except that the composition for the emission layer according to Preparation Example 3 was used instead of the composition for the emission layer according to Preparation Example 1, the emission layer was formed with an average thickness of 30 nm, and the electron transport layer was formed with an average thickness of 60 nm.

[0318] Example 8

[0319] The electroluminescent device according to Example 8 was manufactured according to the same method as Example 1, except that the composition for emission layer according to Preparation Example 3 was used instead of the composition for emission layer according to Preparation Example 1 and the emission layer was formed with an average thickness of 30 nm.

[0320] Example 9

[0321] The electroluminescent device according to Example 9 was manufactured according to the same method as Example 1, except that the composition for an emission layer according to Preparation Example 6 was used instead of the composition for an emission layer according to Preparation Example 1.

[0322] Example 10

[0323] The electroluminescent device according to Example 10 was manufactured according to the same method as Example 1, except that the composition for an emission layer according to Preparation Example 7 was used instead of the composition for an emission layer according to Preparation Example 1.

[0324] Embodiment 11

[0325] The electroluminescent device according to Example 11 was manufactured according to the same method as Example 1, except that the composition for an emission layer according to Preparation Example 8 was used instead of the composition for an emission layer according to Preparation Example 1.

[0326] Example 12

[0327] The electroluminescent device according to Example 12 was manufactured according to the same method as Example 1, except that the composition for an emission layer according to Preparation Example 9 was used instead of the composition for an emission layer according to Preparation Example 1.

[0328] Example 13

[0329] The electroluminescent device according to Example 13 was manufactured according to the same method as Example 1, except that the composition for emission layer according to Preparation Example 7 was used instead of the composition for emission layer according to Preparation Example 1 and the electron transport layer was formed with an average thickness of 60 nm.

[0330] Embodiment 14

[0331] The electroluminescent device according to Example 14 was manufactured according to the same method as Example 1, except that the composition for emission layer according to Preparation Example 8 was used instead of the composition for emission layer according to Preparation Example 1 and the electron transport layer was formed with an average thickness of 60 nm.

[0332] Comparative Example 1

[0333] The electroluminescent device according to Comparative Example 1 was manufactured according to the same method as Example 1, except that the composition for an emission layer according to Comparative Preparation Example 1 was used instead of the composition for an emission layer according to Preparation Example 1.

[0334] Comparative Example 2

[0335] The electroluminescent device according to Comparative Example 2 was manufactured according to the same method as Example 1, except that the composition for emission layer according to Preparation Example 2 was used instead of the composition for emission layer according to Preparation Example 1 and the electron transport layer was formed with an average thickness of 60 nm.

[0336] Evaluation 4: Voltage-current density relationship depending on the content of hole transport material in the emission layer

[0337] The voltage-current density relationships of the electroluminescent devices according to Examples 1 to 4 and Comparative Example 1 and the electroluminescent devices according to Examples 9 to 12 and Comparative Example 2 were measured and are shown in Tables 1 and 2, respectively. Fig.10 and 11 middle.

[0338] Fig.10 is a graph showing the voltage-current density (logarithmic scale) characteristics of the electroluminescent devices according to Examples 1 to 4 and Comparative Example 1 and Fig.11 is a graph showing the voltage-current density (logarithmic scale) characteristics of the electroluminescent devices according to Examples 9 to 12 and Comparative Example 2.

[0339] refer to Fig.10 and 11 , under the predetermined conditions ( Fig.10 as well as Fig.11 In the embodiment 9-12 of the same type of emission layer and the same thickness of the electron transport layer), as the amount of hole transport material in the emission layer increases, the on-state voltage of the device is gradually lower.

[0340] refer to Fig.10 and 11As a result, the electroluminescent device according to the example shows improved hole transporting ability compared with those according to the comparative example, and the hole transporting ability is gradually improved as the amount of the hole transporting material in the emission layer increases.

[0341] Evaluation 5: Relationship between the average thickness of the electron transport layer and device characteristics

[0342] The device characteristics of the electroluminescent devices according to Examples 2, 6, 11, 13 and Comparative Examples 1 and 2 were measured and shown in Table 2.

[0343] (Table 2)

[0344]

[0345] Referring to Table 2, based on the average thickness of the same type of electron transport layer (comparison of Examples 2 and 11 with Comparative Example 1 and comparison of Examples 6 and 13 with Comparative Example 2), depending on the type of hole transport material included in the emission layer, the specific device characteristics may be a little different, but the embodiment shows at least significantly superior maximum brightness (Max brightness) compared to the comparative example. On the other hand, based on the same hole transport material (comparison of Examples 2 and 6 and comparison of Examples 11 and 13), depending on the average thickness of the electron transport layer (ETL), device characteristics such as external quantum efficiency, maximum brightness (Max brightness), etc. may be different.

[0346] On the other hand, the life characteristics of the electroluminescent devices according to Examples 2, 5, 11, and 14 and Comparative Examples 1 and 2 were evaluated respectively and the results are shown in Tables 3 and 4. Figure 8 middle.

[0347] Fig.12 is a graph showing the life characteristics of the electroluminescent devices according to Examples 2, 5, 11, and 14 and Comparative Examples 1 and 2.

[0348] (Table 3)

[0349] T95(h) T50(h) Example 2 0.09 More than 1000 Example 5 0.09 More than 1000 Embodiment 11 154.91 Approx. 700 Embodiment 14 34.35 More than 1000 Comparative Example 1 0.03 4.8 Comparative Example 2 0.03 0.9

[0350] T95 represents the time (h) that elapsed until the brightness becomes 95% of the initial brightness (100%), and T50 represents the time (h) that elapsed until the brightness becomes 50% of the initial brightness (100%).

[0351] refer to Fig.12As shown in Table 3, based on the same electron transport layer thickness (comparison of Examples 2 and 11 with Comparative Example 1 and comparison of Examples 5 and 14 with Comparative Example 2), the electroluminescent device according to the Example shows excellent T50 and T95 compared with those of the Comparative Example. On the other hand, based on the same hole transport material (comparison of Examples 2 and 5 with Comparative Example 1, comparison of Examples 11 and 14 with Comparative Example 2), the lifespan characteristics may also differ depending on the average thickness of the electron transport layer (particularly, refer to Examples 11 and 14).

[0352] Therefore, referring to the results of Evaluation 5, the electron transport layer may have different optimal average thicknesses depending on the kind of the hole transport material included in the emission layer.

[0353] Evaluation 6: Relationship between the average thickness of the electron transport layer and the emission layer and device characteristics

[0354] The device characteristics of the electroluminescent devices according to Examples 3, 6, 7, and 8 and Comparative Examples 1 and 2 were measured, and the results are shown in Table 4.

[0355] (Table 4)

[0356]

[0357] Referring to Table 4, based on the same average thickness of the electron transport layer (comparison of Examples 3 and 8 with Comparative Example 1 and comparison of Examples 6 and 7 with Comparative Example 2), the maximum brightness depending on the average thickness of the emission layer may be opposite to each other. In other words, for Examples 3 and 8, as the average thickness of the emission layer increases, the maximum brightness increases, but for Examples 6 and 7, the maximum brightness decreases. On the other hand, the life characteristics of the electroluminescent devices according to Examples 3, 6, 7, and 8 and Comparative Examples 1 and 2 were evaluated, respectively, and the results are shown in Tables 5 and 6. Fig.13 middle.

[0358] Fig.13 is a graph showing the life characteristics of the electroluminescent devices according to Comparative Examples 1-2 and Examples 3, 6, 7, and 8.

[0359] (Table 5)

[0360]

[0361]

[0362] refer to Fig.13With Table 5, based on the same electron transport layer thickness (comparison of Examples 3 and 8 with Comparative Example 1 and comparison of Examples 6 and 7 with Comparative Example 2), the electroluminescent device according to the embodiment shows excellent T50 and T95 compared with those according to the comparative example. On the other hand, based on the same hole transport material and the same average thickness of the electron transport layer (comparison of Examples 6 and 7 and comparison of Examples 3 and 8) and in particular, with reference to the T95 of Examples 7 and 8, when the thickness of the emission layer changes, the life characteristics may be different. However, the life characteristics of Examples 3, 6, 7, and 8 show an excellent T50 of more than 1000 hours.

[0363] Therefore, referring to the results of Evaluation 6, the average thickness of the emission layer also has an influence on the device characteristics, and therefore, the device characteristics can be adjusted by controlling the average thickness of the electron transport layer and the average thickness of the emission layer.

[0364] While the present disclosure has been described in connection with what are presently considered to be practical example embodiments, it is to be understood that the invention is not limited to the disclosed embodiments, but on the contrary is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.

[0365] <Description of symbols>

[0366] 10: Electroluminescent device 100: Substrate

[0367] 110: first electrode 120: hole injection layer

[0368] 130: hole transport layer 140: emission layer

[0369] 141: Quantum Dots 150: Electron Transport Layer

[0370] 160: Second electrode

Claims

1. Electroluminescent devices, including a first electrode and a second electrode facing each other; an emission layer disposed between the first electrode and the second electrode and comprising quantum dots and a first hole transport material having a substituted or unsubstituted C4-C20 alkyl group attached to a backbone structure; a hole transport layer disposed between the emissive layer and the first electrode and including a second hole transport material; and An electron transport layer is provided between the emission layer and the second electrode, wherein the quantum dots include II-VI compounds, III-V compounds, IV-VI compounds, IV elements or compounds, I-III-VI compounds, I-II-IV-VI compounds, or combinations thereof, wherein the first hole transport material is a non-polymeric material, and The first hole transport material includes a compound represented by Chemical Formula 2: [Chemical formula 2] Wherein in Chemical Formula 2, R 1 -R 8 independently selected from substituted or unsubstituted C4-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, substituted or unsubstituted C6-C20 aryl, substituted or unsubstituted C3-C20 heteroaryl, substituted or unsubstituted C1-C20 alkylamine, substituted or unsubstituted C4-C20 arylamine, and substituted or unsubstituted carbazolyl, with the proviso that R 1 -R 6 At least one of is a substituted or unsubstituted C4-C20 alkyl group, When R 3 -R 6 When it is one of a substituted or unsubstituted C3-C20 cycloalkyl group, a substituted or unsubstituted C6-C20 aryl group, or a substituted or unsubstituted C3-C20 heteroaryl group, they are fused with the adjacent aromatic ring to provide a C8-C40 fused ring, X 3 and X 4 Independently selected from S, NR b , and C(-R c )(-R d ), where R b , R c , and R d is independently selected from substituted or unsubstituted C1-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, substituted or unsubstituted C6-C20 aryl, and substituted or unsubstituted C3-C20 heteroaryl, L 1 and L 2 are independently selected from a single bond and a substituted or unsubstituted methylene or C2-C4 alkenylene, and j, k, l, and m are independently 0 or 1, or The first hole transport material includes at least one of the compounds represented by Chemical Formulas B to D and F: [Chemical formula B] [Chemical formula C] [Chemical formula D] [Chemical formula F] 2. The electroluminescent device according to claim 1, wherein R 1 -R 6 At least two of the groups are substituted or unsubstituted C4-C20 alkyl groups.

3. The electroluminescent device according to claim 1, wherein the first hole transport material comprises at least one of the compounds represented by Chemical Formula 2-1 to Chemical Formula 2-2: [Chemical formula 2-1] [Chemical formula 2-2] in, In Chemical Formula 2-1 to Chemical Formula 2-2, X 3 and X 4 Independently the same as defined in Chemical Formula 2 of claim 2, R 11 , R 12 , R 13 , R 14 , R 15 , R 16 , R 21 , R 22 , R 23 , R 24 , R 25 , and R 26 are independently selected from substituted or unsubstituted C4-C20 alkyl, substituted or unsubstituted C3-C20 cycloalkyl, substituted or unsubstituted C6-C20 aryl, and substituted or unsubstituted C3-C20 heteroaryl, with the proviso that R 11 -R 14 At least one and R 21 -R 26 At least one of is a substituted or unsubstituted C4-C20 alkyl group, R 27 and R 28 independently selected from substituted or unsubstituted C1-C20 alkylamine groups, substituted or unsubstituted C4-C20 arylamine groups, and substituted or unsubstituted carbazolyl groups, and When R 13 , R 14 , R 15 , R 16 , R 23 , R 24 , R 25 , and R 26 When it is one of a substituted or unsubstituted C3-C20 cycloalkyl group, a substituted or unsubstituted C6-C20 aryl group, or a substituted or unsubstituted C3-C20 heteroaryl group, they are condensed with the adjacent aromatic ring to provide a C8-C40 condensed ring.

4. The electroluminescent device of claim 1, wherein the first hole transport material has solubility in a non-polar solvent. 5 . The electroluminescent device of claim 1 , wherein the first hole transport material is included in an amount greater than or equal to 2 wt % and less than 50 wt % based on 100 wt % of the total weight of the emission layer.

6. The electroluminescent device of claim 1, wherein the root mean square roughness of the surface of the emission layer measured by atomic force microscopy is 0.5-2.

0. The electroluminescent device of claim 1 , wherein a hydrophobic ligand is bound to the surface of the quantum dots. The electroluminescent device of claim 1 , wherein the quantum dots have a core-shell structure.

9. The electroluminescent device of claim 1, wherein the second hole transport material and the first hole transport material are different materials.

10. The electroluminescent device of claim 9, wherein the second hole transport material comprises poly(3,4-ethylenedioxythiophene) or a derivative thereof, poly(styrene sulfonate) or a derivative thereof, poly-N-vinylcarbazole or a derivative thereof, polyphenylenevinylene or a derivative thereof, polyparaphenylenevinylene or a derivative thereof, polymethacrylate, polyarylamine, polyaniline or a derivative thereof, polypyrrole or a derivative thereof, poly(9,9-dioctylfluorene) or a derivative thereof, poly(spiro-bifluorene) or a derivative thereof. ) or its derivatives, poly-(N,N'-diphenyl-N,N'-di(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine), poly[(9,9-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-4-butylphenyl)diphenylamine], poly[(9,9-dioctylfluorene)-co-(N,N'-diphenyl-N,N'-di-(p-butylphenyl)-1,4-diaminobenzene)], NiO, MoO3, or a combination thereof.

11. The electroluminescent device of claim 1, wherein the electron transport layer comprises inorganic material nanoparticles, quinolone-based compounds, triazine-based compounds, quinoline-based compounds, triazole-based compounds, naphthalene-based compounds, or a combination thereof.

12. The electroluminescent device of claim 11, wherein the electron transport layer comprises a cluster layer composed of inorganic material nanoparticles.

13. The electroluminescent device of claim 1, wherein the electron transport layer has a thickness of 20 nm to 100 nm.

14. The electroluminescent device of claim 1, wherein the electroluminescent device further comprises a hole injection layer between the first electrode and the hole transport layer.

15. A display device comprising the electroluminescent device according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Antibody specifically binding to MUC1 and Use thereof

    KR1020180107005A

  • Color display device based on quantum dot electroluminescent devices

    CN106997890A

  • Organic electroluminescent element

    JP1993025473A

  • Method for manufacturing electroluminescence element

    US20090087792A1

  • Light-emitting device, display device, electronic device, and lighting device

    US20170213876A1